Detection of genes of pathogenicity of symbiotic microflora in adjacent biotopes in women with chronic endometritis and reproductive disorders - E. A. Kungurtseva (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
Recent researches established microecological relationships between intestinal, vaginal and nasopharyngeal biocenoses in the composition of a macroorganism microbiome. This study included 57 women with chronic endometritis and 21 woman without it (control group). In women with chronic endometritis all studied pathogenicity genes (asal, cylA, stxl and stx2) were identified in representatives of symbiotic microflora in all three studied habitats - vaginal, intestinal and nasopharyngeal, which confirms the presence of a reservoir of potential pathogenicity. Studied genes of pathogenicity were diagnosed in women with CE in 8 cases of the bacteria of the species E. faecalis and E. faecium, which are "harbingers" of impending serious problem. This indicates the importance of these species in etiopathogenetic structure of microbiocenoses of studied habitats, and, possibly, their impact on the course of this disease.